Subject of crime - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2020)
The lecture of academic discipline "Criminal Law (General Part)" for students of National University "Odessa Law Academy".
Tuliakov V. Subject of crime : video lecture / V. Tuliakov. - Odessa, 2020. - Access mode: https://youtu.be/0_ux44l2Yr8
Keywords: criminal law; кримінальне право; уголовное право